PENGARUH NILAI-NILAI TUNJUK AJAR UNTUK MENINGKATKAN HUBUNGAN SOSIAL SISWA MELALUI BIMBINGAN KELOMPOK DI SMK MUHAMADIYAH 1 PEKANBARU - Nurhapizah Nurhapizah; Zulfan Saam; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: Social relations are the core of the realization of social life because without social relations, individuals will not be able to run their lives well. This study aims to describe the social relations of students before and after being given Teachers 'Values through group guidance, to determine differences in social relations before and after being treated with Teachers' Point Values through group guidance and to determine the influence of Teachers Point Values through group guidance to improve student social relations. This research is a quantitative research with an experimental method, the research design used is the Pre-Experimental approach with one group pre-test and the post test subject in this study were 7 students taken by purposive sampling technique with the results of the questionnaire. The results showed that: (1) the social relations of students before being given Teachers 'Point Values through group guidance were mostly in the low category and after being given Teachers' Point Values through group guidance most of them were in the high and medium categories. (2) There are significant differences in the level of student social relations before and after being given Teacher's Value through group guidance. (3) There is a significant effect of students 'social relations before and after being given Teachers' Point Values through group guidance. Key Words: Tunjuk Ajar, Social Relations, Group Guidance